Penerapan Business Model Canvas (BMC) dalam Menumbuhkan Pola Pikir Kewirausahaan Mahasiswa - Rezvanny maricar; Syahribulan Syahribulan; Rosmiati Rosmiati (Economy Deposit Journal (E-DJ), 2022)
The purpose of this research is to learn more about the business model canvas (BMC) and how it may be used to help students develop an entrepreneurial attitude. The BMC technique for both corporations and organizations is becoming increasingly popular in examining startups or businesses to show the business entity. Action This study's research reveals the most effective and efficient method for demonstrating a gain in performance or learning. This study is both qualitative and quantitative in nature. A questionnaire was completed by 30 students who had taken entrepreneurial classes. The results suggested that using the BMC method could help students develop a more entrepreneurial mindset. The BMC technique allows students to be recognized, taught, and utilized in entrepreneurship courses and practices